The impact of the neoliberal technological epoch and Covid-19 on the decolonization of the university curriculum - Koopman, O.; Koopman, K. J. (South African Journal of Higher Education, 2021)
In this article we will argue that South Africa’s capitalist neoliberal agenda for higher education, where the focus is on the shift from a knowledge economy to a digital economy, will choke the life of indigenous knowledge out of the university curriculum. To support this claim the article discusses, firstly, the impact of the core neoliberal ideals on the university curriculum landscape. Secondly, drawing on the scholarly work of Martin Heidegger and his anticipation of the spirit of the time in the technological epoch, the article shows how humans in this era will be viewed as a heap of fungible raw materials, resources, or standing reserve (Bestand) awaiting optimisation. In this technological age knowledge is subject to the demands of the market, where the focus will be exclusively on knowledge that has a utilitarian value in and impact on the technological epoch. A direct consequence of this is that little space will be provided for the inclusion of indigenous knowledge in the curriculum. We conclude by showing how the current Covid-19 pandemic dismissed the voices and disregarded the efforts of indigenous healers in the fight against the pandemic. All these developments illustrate government’s power to impose its neoliberal agenda on the university that will ultimately lead to the detriment and neglect of indigenous knowledge.